2016
DOI: 10.1177/1054773815626667
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Among Jordanian Adolescents

Abstract: Adolescence is an unpredictable stage of life with varied and rapid changes. In Jordan, health-related quality of life (HRQoL) has been examined among diabetic and obese children and adolescents. The purpose of this study was to assess the HRQoL of Jordanian healthy adolescents. Three hundred fifty-four male and female adolescents whose ages ranged from 12 to 19 participated in the study. A descriptive comparative design was employed to investigate adolescents' HRQoL. The results revealed statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
(51 reference statements)
4
11
0
Order By: Relevance
“…Girls reported a significantly lower HRQoL than boys at both measurement points. This finding is consistent with those of previous studies of gender differences between girls and boys, with girls reporting lower HRQoL than boys (Hourani et al, ; Limperg et al, ; Meyer et al, ; Ravens‐Sieberer et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Girls reported a significantly lower HRQoL than boys at both measurement points. This finding is consistent with those of previous studies of gender differences between girls and boys, with girls reporting lower HRQoL than boys (Hourani et al, ; Limperg et al, ; Meyer et al, ; Ravens‐Sieberer et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Adolescents generally have good health and HRQoL, but there remain health challenges in the adolescent population (Patton et al, ; WHO, , ). Previous studies have indicated gender differences and found that girls tend to report lower HRQoL than boys (Hourani, Hammad, Shaheen, & Amre, ; Limperg et al, ; Meyer, Oberhoffer, Hock, Giegerich, & Müller, ; Ravens‐Sieberer et al, ). Studies have also found that self‐reported mental health problems are related to decrease HRQoL (Otto et al, ; Sharpe et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…The outpatient group scores were significantly higher than inpatient scores in all domains except for the school functioning, where the inpatient group score was significantly higher. Both groups scored highest in social functioning; the (Hourani et al, 2017). Our results also concur with results from Turkish population using the same investigation instrument (Arslan et al, 2013).…”
Section: Pedsql 40 Generic Core Scores For Inpatients Vs Outpatientssupporting
confidence: 89%
“…Although a study on HRQOL in Jordanian adolescents with overweight or obesity revealed that overweight/obese females had poorer QOL in all domains (Al-Akour et al, 2012), studies on gender differences in school performance among adolescents diagnosed with cancer or other chronic illness are scarce. A study on quality of life in healthy Jordanian adolescents did not find significant differences between males and females on the school environment domain (Hourani et al, 2017). However, a study by Klatchoian et al on Brazilian children found that healthy female adolescents scored higher in the school dimension (Klatchoian et al, 2010).…”
Section: Pedsql 40 Generic Core Scores For Inpatients Vs Outpatientsmentioning
confidence: 91%
“…Research on health-related quality of life (HRQoL) has increased in the last years 1, 2, 3, 4, 5. HRQoL can be defined as a multidimensional construct that relates to a person's self-perceived health and consists of ratings of well-being and functionality in important life areas, including physical well-being/functioning, emotional well-being, self-esteem, social functioning, and family relations 2 .…”
Section: Introductionmentioning
confidence: 99%